INTRODUCTIONS OF IGNORANCE OF THE ABBASID BALOFUAH - ABDUL RAHMAN ZAYED, ENAS (Journal of College of Education, 2020)
ENAS ABDUL RAHMAN ZAYEDAbstractThe introduction is a living example of the poets of the Ignorant Era, it is a feature of their poems that characterized them, and a fundamental opening for each poet in his poem, and in the Abbasid era he took those who advocated the idea of getting rid of those introductions and leaving them, because they had nothing to do with their era, but some of them opened their Abbasid poems. With similar introductions with ignorant introductions, I saw these demand features from Abbasid poets. I divided the research after the summary into an introduction and two topics i explained in the introduction what the introduction in all its eras and what the developments in it have brought, but the first topic was our talk about conflicts between supporters and rejectionists, and the second topic explained the most important reasons that called on a civilized Abbasid poet to stick to it. The old tradition, and then the Abbasid evidence sought to match the ignorant evidence, and then concluded with a seal in which I explained the most important findings I reached, and then proved the list of margins and their sources.